Contribution of Cedomir Milic to education of Sokol staff in Herzegovina - Kristina Pantelić Babić; Petar Pavlović (University of Banja Luka, Faculty of physical education and sport, 2013)
Cedomir Milic, from father Jovan Milic and mother Soka Milic (maiden Govedarica), was born on March 23rd 1886 in Mostar, and killed on November 22nd 1941 near Niksic. Since the founding of first Serbian gymnastic society "Obilic" in Mostar in 1904 (since 1910 known as "Serbian Sokol (hawk)"), Milic was involved in its work and dedicated his whole life to sokol and national work. Through sokol and fraternity societies he fought for spiritual and physical strengthening of his people. He was deeply respected, not only by sokols and brothers (members of the fraternity), but also by the intellectuals of that time. Among his numerous sokol activities, he also gave great contribution to education and specialization of sokol staff on the territory of Herzegovina during Austro-Hungarian occupation, and also in Sokolism in the time of Kingdom of Serbs, Croats and Slovenians (since 1929 Kingdom of Yugoslavia). The goal is to highlight and research the role of Cedomir Milic in education and specialization of sokol staff. Numerous sources from the time of Milic's life and work, as also sources originated after that, were reviewed and analyzed.